The Role of Pancasila and Partipation In National Problems - Yuniarto, Bambang; Safitri, Azzahra Nur; Maola, Dia Hasbi; Iman, Sopian Nur; Devi, Devi (Advances In Social Humanities Research, 2023)
This research discusses the topic "The Role of Pancasila in Participation in National Problems" For this reason, Pancasila plays an important role in participating in and solving the problems of the Indonesian nation. As the foundation of the state, Pancasila offers basic values and principles that lead to unity, justice, and prosperity. Pancasila values such as gotong royong, welfare, justice, and unity can encourage people to actively participate in solving state problems. This research provides an overview of how Indonesia's national ideology can be a foundation to encourage active participation in answering the nation's problems. The methodology of this study uses a qualitative approach, and the system used in this study is a descriptive method that describes, describes, and says to solve problems. This journal uses literature research. Library research is research in which authors collect and consolidate information from multiple sources. Sources include books and websites. Literature research is used as the first step of research to determine the research topic, and in this study, it is used as research material and further analysis to obtain research results. The main idea of the discussion is to provide information and add a broader point of view.